Beyond the endorsement of reflection in language teaching and learning - Cuesta Medina, Liliana; Alvarez Ayure, Claudia Patricia; Cadena Aguilar, Albedro; Jiménez Bonilla, Maria Sonia; Maldonado Chacón, Pedro Pablo; Morales Pulido, Virginia (Colombian Applied Linguistics Journal, 2019)
This paper reports on the first phase of an exploratory qualitative study carried out with in-service language teachers pursuing a graduate degree in Colombia. It aims at analyzing their practices, needs, and challenges, examined under two perspectives—the teacher as a learner and the teacher as a teacher. The study made use of interviews, focus groups, and questionnaires as the primary sources of data. Data analysis included a grounded theory approach and the use of coding, triangulation, and validation procedures. Results unveiled the difficulties that current in-service teachers have in different domains (cognitive, metacognitive, and linguistic), and also inform how the teaching challenges within their specific contexts influence their beliefs, practices, learning and teaching outcomes, and their professional growth. The study presents both theoretical and applied considerations to tackle the needs and challenges reported, aiming at offering a systematic analysis and approach for the endorsement of reflection, and thus, setting milestones for the enhancement of effective professional development for language teachers in educational communities such as in Colombia as well as overseas.